Non-destructive evaluation of depth, thickness and composition of single ZnCdSe nanolayers buried in II-VI heterostructures. (October 2018) - Karavaev, M.B.; Ivanova, E.V.; Popova, T.B.; Ivanov, S.V.; Zamoryanskaya, M.V.
Abstract: Wide-gap ZnSe-based nanoheterostructures grown by molecular beam epitaxy are comprehensively studied by electron probe microanalysis and local cathodoluminescence techniques. These non-destructive methods applied in combination allow independent determination of true depth, composition, and thickness of single ZnCdSe nanolayers (NL), located deep inside the heterostructures, with a relative accuracy of 10%. The developed approach is based on the variation of the electron probe energy, which results in different thickness of the region where characteristic x-ray emission and cathodoluminescence occur. The former establishes relation between the NL depth and composition at a fixed NL thickness, as defined by using an original modelling program, while the latter connects the NL thickness and composition. Highlights: Non-destructive evaluation of all parameters of a single nanolayer buried in a heterostructures. Modeling of variable-electron-energy EPMA data in combination with CL spectra. The relative accuracy of determination of depth, thickness, and composition is better than 10%.